Directed solid-phase synthesis of trisubstituted imidazo[4,5-c]pyridines and imidazo[4,5-b]pyridines - Lemrová, Barbora; Smyslová, Petra; Popa, Igor; Oždian, Tomáš; Zajdel, Pawel; Soural, Miroslav (ACS combinatorial science, 2014)
An efficient method is described for the solid-supported synthesis of imidazo[4,5-b]pyridines and imidazo[4,5-c]pyridines from 2,4-dichloro-3-nitropyridine. The key pyridine building block was reacted with polymer-supported amines, followed by replacement of the second chlorine with amines, nitro group reduction, and imidazole ring closure with aldehydes. Depending on the combination of polymer-supported and solution-phase reagents, the strategy allowed for the simple preparation of the target trisubstituted derivatives with variable positioning of the pyridine nitrogen atom. Additionally, after a slight modification of the method, the preparation of strictly isomeric imidazopyridines was possible.
Keywords: imidazo[4,5-c]pyridines; Imidazoles; imidazoly; solid-phase synthesis; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; techniky syntézy na pevné fázi; Solid-Phase Synthesis Techniques; Pyridines; 3-deazapurines; Isomerism; pyridiny; 1-deazapurines; 2,4-dichloronitropyridine; aldehydy; imidazo[4,5-b]pyridines; isomerie; indikátory a reagencie; Aldehydes; Indicators and Reagents